Flightless Catapionus (Coleoptera: Curculionidae: Entiminae) in Southwest China survive the Holocene trapped on mountaintops: new species, unknown phylogeny and clogging taxonomy - Grebennikov, Vasily V. (Zootaxa, 2016)
This paper reports the first discovery of the weevil genus Catapionus in Southwest China. Eighteen specimens of C. mopsus sp.n. were collected in two high altitude localities some 360 km apart: Mt. Haba in Yunnan (the type locality) at 4,158–4,195 m and Mt. Gongga in Sichuan at 3,533–4,143 m. Habitus and genitalia of a male and a female from each locality are extensively illustrated. Six specimens from each locality were DNA barcoded (dx.doi.org/10.5883/DS-CATAPCH). Taxonomic validation of the new species name was made by referring to high quality illustrations of the holotype and to its DNA barcode, and without providing a customary verbal description. This novel approach was chosen partly due to the redundancy of description in the presence of high quality images, and partly due to the lack of adequate and unambiguously identified comparative material. Analysis of mtDNA sequences dated the separation of both geographical populations at about 3.65 Ma. The disjunct distribution of Catapionus in Asia is discussed and mapped for the first time. Monophyly and internal relationships of the genus are discussed and remain untested, together with the generic assignment to the phylogenetically vague Cneorhinini and/or Dermatodini. Discovery of the southernmost members of Catapionus high in the mountains of Southwest China evokes a hypothesis on interglacial refugia. A new term “clogging taxonomy” is introduced for situations as encountered in Catapionus when an abundance of obscure historical species-group names impedes further research.